Influence of Childhood Family Routines on Adult Depression: A Cross Sectional Study - Yan, Yuzhi; Zhang, Junyi; Dong, Shenghong (Frontiers in Psychology, 2021)
In order to explore the influence of childhood family routines on adult depression and the mediating role of tolerance of uncertainty and rumination, the current study tested 818 participants by adopting four questionnaires. The results of structural equation modeling revealed that (1) family routines had a negative effect on depression among Chinese college students; (2) family routines were found to have a positive effect on tolerance of uncertainty, and tolerance of uncertainty was a bridge linking family routines and depression; (3) family routines had a significant effect on depression through rumination; (4) the relationship between family routines and depression was partially mediated by the chain of tolerance of uncertainty and rumination. The result reveals not only the fact that childhood family routines have significant influence on college students' depression but also the mechanism of childhood family routines that affect college students' depression. The limitations and implications of our study were also discussed.